FPGA basic multi-modulation processor design [microfilm] - Nooraini Mohamed (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Telecommunication)) - Universiti Teknologi Malaysia, 2001